BS ISO 15592-3. Fine-cut tobacco and smoking articles made from it. Methods of sampling, conditioning and analysis. Part 3. Determination of total particulate matter of smoking articles using a routine analytical smoking machine, preparation for the determination of water and nicotine, and calculation of nicotine-free dry particulate matter (23rd March 2022) - British Standards Institution,
No abstract available